Removal of methylene blue dye using Nostoc commune biomass: Kinetic, equilibrium and thermodynamic study - Lavado-Meza, C. (2021)
In the present work, the elimination of the cationic Methylene Blue (MB) dye is reported using the dry powder of nostoc commune (NC). The results of the Fourier Transform Infrared Spectroscopy (FTIR) analysis corroborated the presence of functional groups such as hydroxyls, carbonyls, and amines, which would be associated with the removal of MB. In a stationary (batch) system, the experimental parameters that affect biosorption, such as NC dose, pH, temperature, and initial MB concentration were evaluated. The experimental data of the isotherm fit better to the Langmuir model. The maximum biosorption capacity of MB of 158.7 mg/g was obtained with a dose of 1 g/L, pH 8, and contact time of 120 min. The kinetic data were better adjusted to the pseudo-second-order model, which indicates that biosorption seems to be controlled by chemisorption, the intraparticular diffusion model indicates that diffusion in the pores is the limiting factor throughout the biosorption process. The thermodynamic parameters indicated that at all the temperatures evaluated (293, 303, and 313 K) the biosorption of MB on NC was a spontaneous, favorable, and exothermic process. The results showed that NC can be used to remove cationic dyes from wastewater.